Two new species of Scutellaria (Lamiaceae) from Thailand and Burma. Issue 1 (March 2016) - Paton, Alan; Suddee, Somran; Bongcheewin, Bhanubong
Summary Two new species ofScutellaria (Lamiaceae), S. tenasserimensis A. J. Paton andS. khaoyaiensis A. J. Paton, are described here. The nameS. cana Wall. ex Benth., recognised as a synonym ofS. repens D. Don, is based on specimens belonging toS. repens andS. tenasserimensis. S. cana is lectotypified to clarify the division of these two species. A key to theScutellaria species of Thailand is provided and the relationships of the species and the relevant morphological characters, particularly nutlets, are discussed.